Protection against malaria in heterozygous girls for G6PD deficiency in Angola - Brito, Miguel (2019)
G6PD deficiency has become more prevalent in malaria-endemic regions because genetic variants can confer protection against Plasmodium. However, these conclusions are still in debate. The aim of this work is to evaluate the prevalence of G6PD deficiency in an African holoendemic region for Plasmodium falciparum, estimating the genotype and phenotype of the enzyme, and evaluating the risk of malaria associated with the G6PD genotype. A prospective longitudinal cohort study, involving 1692 children selected in the maternity ward and monitored over quarterly medical consultations for two years. The G202A and A376G genotypes were determined through Real-Time PCR methods. For enzyme activity, we applied the NeoLISA kit for Neonatal G6PD deficiency screening to measure the NADPH produced calorimetrically in the kinetic model. The prevalence of the A-allele was 19.4%, with 19% hemizygous boys and 4.5% A-homozygous girls. Enzyme deficiency, measured by enzyme activity, was highly prevalent (32.7% in males and 30.5% in females). The average enzymatic activity was also low for A-hemizygous boys (1.66U/gHb) and for homozygous girls (0. 97U/gHb). Heterozygous girls would seem to hold some protection against malaria when compared to the other genotypes, mainly A-/A- (X2=14.35, p=0.014). The prevalence of G6PD deficiency among children in Bengo is high. Heterozygous girls, as proposed elsewhere, maybe the driving force for positive selection. This data may serve the ministry of health in taking safe and appropriate decisions regarding the usage of potentially unsafe drugs for G6PD deficient individuals.